Analisis Level Berpikir Geometri Guru MI Ditinjau dari Jenis Kelamin - Mohammad Auzai Aqib (eL Bidayah: Journal of Islamic Elementary Education, 2019)
One of the scopes of mathematical material for MI is geometry and measurement. So many competencies related to geometry for basic education units are their own difficulties for students. The students' difficulties in learning geometry is certainly a challenge for teachers who are given the task of teaching the subjects concerned. In essence, the teacher must have professional competence where the teacher must master the material taught. The level of mastery of the material especially geometry can be seen from the level of thinking of Van Hielle's teacher. This study aims to describe the level of thinking of male and female MI teachers. This type of research is a descriptive study with a qualitative approach. The subjects in this study were male and female MI teachers who both taught class VI to avoid bias. The instruments in this study were the researchers themselves and test-based interview guidelines. The test given is adapted from V.H.G.T (Van Hielle Geometry Test). Data processing is done by reducing data, presenting data, and drawing conclusions. The results showed that the level of thinking of male MI teacher geometry was at level 0 while the level of thinking of the geometry of female MI teachers was at level 2.